STUDIES ON PHYSICO-CHEMICAL, MICROBIOLOGICAL AND SENSORY EVALUATION OF MANGO PULP STORAGE WITH CHEMICAL PRESERVATIVES - Hussain, arfraz; Saleem-ur-Rehman; Randhawa, M. Atif; Iqbal, Muhammad (Journal of Research (Science), 2003)
Mango pulp was preserved with the help of chemical preservatives as potassium metabisulphite (KMS), sodium benzoate (SB) and potassium sorbate (PS) singly or in various combinations. The pulp samples were partially pasteurized at 82 ± 2 °C for 30 minutes and placed in high-density polyethylene bags with addition of chemicals and kept at 30-45 °C for 150 days. The pulp was tested for physico-chemical, microbiological and sensory characteristics. It was found that chemical treatment containing KMS 1000 ppm, SB 500 ppm and PS 400 ppm was effective against microorganisms and no colonies were formed up to 90 days of storage period. These samples were also physically and organoleptically normal even after 270 days. It was found that pasteurized mango pulp could be stored for extended period of time without any major changes in chemical composition and sensory characteristics.